Compute Function Analysis Utilizing IAAS Private Cloud Computing Service Model in Packstack Development - Suriansyah, Mohamad Iqbal; Mulyana, Iyan; Sanger, Junaidy Budi; Winata, Sandi (ILKOM Jurnal Ilmiah, 2021)
Development of packstack for compute function analysis with IAAS serviceÂ  Analysis of computational functions by utilizing the IAAS model for private cloud computing services in Packstack is one of the large-scale data storage solutions. Problems that often occur when implementing various applications are server resource requirements, monitoring processes that are less than optimal, offering that is limited in time when building servers, and when upgrading hardware devices will have an impact on server downtime that quite long. The development of private cloud computing technology can be one solution to the problem in question. This study utilizes Openstack and Packstack by applying a single node server controller with 2 compute server nodes. Administration server with IAAS service approach and self-service. The scalability testing is simple and more time-efficient. Change the size of the virtual server (instance) developed in a more optimal running condition for measuring overhead values in private cloud computing with a downtime of 16 seconds.